Guinea pigs raised as livestock are incidental host of Toxoplasma gondii and Influenza A in Ecuador - Salas-Rueda, Mauricio Xavier; Peralta-Ortiz, Patricia; Guama-Tipas, Jairo; Chávez Toledo, Katherine Natalia; Espadero, Mónica; Webster, Pedro; Masache-Masache, Juan; Illescas Sigcha, Karla Monica; Yungazaca Jaramillo, Fabiola Estefania; Rodríguez-Pazmiño, Angel Sebastian; Alcivar, Fabricio Arcos; Orlando, Solon Alberto; et al. (Frontiers in Veterinary Science, 2025)
The guinea pig (Cavia porcellus) is commonly used as a laboratory model or kept as a pet in many Western countries; however, in Andean countries like Ecuador, it is raised as livestock. Despite its importance to rural local economies, specific management guidelines for guinea pig farming have not been enforced by animal or public health authorities. Several reports indicate that guinea pigs raised as livestock serve as incidental host for respiratory and enteric pathogens, including Toxoplasma gondii. This study analysed the seroprevalence of antibodies against several pathogens relevant to public health and animal production in Ecuador: Influenza A, Brucella spp., Coxiella burnetii, Toxoplasma gondii, and Neospora caninum. Blood samples from 240 guinea pigs were collected in the cantons of Cuenca, Paute, and Gualaceo, in the Azuay province of Ecuador. Seropositive animals were detected for two pathogens—Influenza A and T. gondii—with prevalence rates of 1.67% (95% CI: 0.46–4.21) and 16.25% (95% CI: 11.82–21.54), respectively. There were not seropositive animals for Brucella spp., Coxiella burnetii and Neospora caninum. These results underscore the potential role of guinea pigs as incidental host for Influenza A and support their inclusion in surveillance programs for panzootic flu outbreaks. Additionally, guinea pigs may play a significant role in the epidemiology of toxoplasmosis in the Andean regions of Ecuador, Peru, and Colombia, where similar findings have been reported.